2009
DOI: 10.1007/s00264-009-0778-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and histological comparison of the influence of oestrogen deficient state on tendon healing potential in rats

Abstract: Thirty-six female Sprague-Dawley rats were divided into two groups: oophrectomised (oestrogen deficient) rats and sham operated (oestrogen maintained) rats. Rats were sacrificed at six, ten, and 14 weeks. The rats were randomly chosen to have biomechanical evaluation on one side and histological evaluation on the other. Biomechanical testing was performed on an Instron machine to measure peak load. Histological sections were evaluated for cell proliferation, collagen-fibre organisation, fibroblast density, ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…Additionally, all FDL repairs were conducted with male mice only, limiting assessment of potential sex differences in the healing response, a potentially important factor given that estrogen deficiency decreases the maximum stress of healing Achilles tendons. 50 Here, we demonstrate that mechanical properties of the FDL, FCU, and tail tendon fascicles are not altered as a function of sex or age, however, alterations in ECM composition and structure occur with aging in the FDL. Moreover, flexor tendon healing is impaired in aged mice due to a decrease in matrix deposition, resulting in decreased mechanical properties.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Additionally, all FDL repairs were conducted with male mice only, limiting assessment of potential sex differences in the healing response, a potentially important factor given that estrogen deficiency decreases the maximum stress of healing Achilles tendons. 50 Here, we demonstrate that mechanical properties of the FDL, FCU, and tail tendon fascicles are not altered as a function of sex or age, however, alterations in ECM composition and structure occur with aging in the FDL. Moreover, flexor tendon healing is impaired in aged mice due to a decrease in matrix deposition, resulting in decreased mechanical properties.…”
Section: Discussionmentioning
confidence: 62%
“…Since it has been shown that the location and function of the tendon influences its response to aging/healing, examination of a wider range of tendons would give a more comprehensive picture of the effects of aging on tendons. Additionally, all FDL repairs were conducted with male mice only, limiting assessment of potential sex differences in the healing response, a potentially important factor given that estrogen deficiency decreases the maximum stress of healing Achilles tendons …”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports show an increased susceptibility to tendon injury in young women, 35<37 whereas in postM women, an increased cross-sectional area of Achilles tendon has been observed by Magnusson et al, 1 and the beneficial effects of HT on Achilles tendon have been reported only in physically active postM women, but not in sedentary controls. 2,38 In experimental models of surgical menopause in rats and rabbits, alterations in cell metabolism 39 and reduced tendon cell proliferation 40 have been observed in comparison with sham-operated animals. Based on these data, the hypothesis that tendon integrity may be compromised directly by estrogen decline may be supposed, but not definitely affirmed.…”
Section: Discussionmentioning
confidence: 98%
“…The Achilles tendon was repaired by using 6/0 ethilon monofi lament nylon sutures. The wound was closed with 3/0 ethilon monofi lament uninterrupted sutures (10). The rats were allowed free cage movement immediately after surgery.…”
Section: Surgery Protocolmentioning
confidence: 99%